Inclusion of dasyochloa in the amphitropical genus Munroa (Poaceae, Chloridoideae) based on morphological evidence - Amarilla, Leonardo (2013)
Munroa is a morphologically heterogeneous American genus of grasses, including five species with disjunct distribution in North and South America. Dasyochloa is a monotypic grass genus, common in western North America, with a controversial taxonomic position, because it has been alternatively included in Erioneuron, Koeleria, Triodia, and Uralepis. We evaluated the relationship of Dasyochloa with Munroa using a phylogenetic analysis of qualitative and quantitative morphological data. Dasyochloa was not supported as an independent genus from Munroa, as Dasyochloa and Munroa species formed a monophyletic group defined by seven synapomorphies. On this basis, we transfer Dasyochloa to Munroa, and propose the new combination M. pulchella together with the emended diagnosis of Munroa.